Trivalent nucleoside-modified mRNA vaccine yields durable memory B cell protection against genital herpes in preclinical models - Awasthi, Sita; Knox, James J.; Desmond, Angela; Alameh, Mohamad-Gabriel; Gaudette, Brian T.; Lubinski, John M.; Naughton, Alexis; Hook, Lauren M.; Egan, Kevin P.; Tam, Ying K.; Pardi, Norbert; Allman, David; et al. (The Journal of Clinical Investigation, 2021)
Nucleoside-modified mRNA vaccines have gained global attention because of COVID-19. We evaluated a similar vaccine approach for preventing a chronic, latent genital infection rather than an acute respiratory infection. We used animal models to compare an HSV-2 trivalent nucleoside-modified mRNA vaccine with the same antigens prepared as proteins, with an emphasis on antigen-specific memory B cell responses and immune correlates of protection. In guinea pigs, serum neutralizing-antibody titers were higher at 1 month and declined far less by 8 months in mRNA- compared with protein-immunized animals. Both vaccines protected against death and genital lesions when infected 1 month after immunization; however, protection was more durable in the mRNA group compared with the protein group when infected after 8 months, an interval representing greater than 15% of the animal’s lifespan. Serum and vaginal neutralizing-antibody titers correlated with protection against infection, as measured by genital lesions and vaginal virus titers 2 days after infection. In mice, the mRNA vaccine generated more antigen-specific memory B cells than the protein vaccine at early times after immunization that persisted for up to 1 year. High neutralizing titers and robust B cell immune memory likely explain the more durable protection by the HSV-2 mRNA vaccine.